PENGHAPUSAN PERTANGGUNGJAWABAN PIDANA PELAKU PEMBELAAN DIRI YANG MENGAKIBATKAN HILANGNYA NYAWA ORANG (Analisis Yuridis Putusan Nomor 61/Pid.B/2019/PN. Cbd) - Raynaldo, Dino (Universitas Harapan Medan, 2023)
Ccompulsory defence, an act justifying self-defense in the event of a sudden attack or threat of attack; however, the law cannot justify all forms of nature and method of defense and cannot reasonably limit defense. In other words, rational defense is an attack or threat. . In writing this paper I will examine secondary data through case analysis using library research methods, but the type of research data is secondary data. Legislation to rule out self-defense offenses that result in the death of another person is regulated in Article 49 (1) and (2) of the Criminal Code. Law enforcement that overrides the perpetrator's criminal responsibility in self-defense that results in the death of another person, the defendant's actions against the law, and the defendant's resistance in the form of forced or emergency defense. Decision Number 61/Pid.B/2019/PN. The CBD stated that the act was not a crime, so the accused must be acquitted of all charges.